Reconciling Electrostatic and n→π* Orbital Contributions in Carbonyl Interactions. (1st July 2020) - Muchowska, Kamila B.; Pascoe, Dominic J.; Borsley, Stefan; Smolyar, Ivan V.; Mati, Ioulia K.; Adam, Catherine; Nichol, Gary S.; Ling, Kenneth B.; Cockroft, Scott L.
Abstract: Interactions between carbonyl groups are prevalent in protein structures. Earlier investigations identified dominant electrostatic dipolar interactions, while others implicated lone pair n→π* orbital delocalisation. Here these observations are reconciled. A combined experimental and computational approach confirmed the dominance of electrostatic interactions in a new series of synthetic molecular balances, while also highlighting the distance‐dependent observation of inductive polarisation manifested by n→π* orbital delocalisation. Computational fiSAPT energy decomposition and natural bonding orbital analyses correlated with experimental data to reveal the contexts in which short‐range inductive polarisation augment electrostatic dipolar interactions. Thus, we provide a framework for reconciling the context dependency of the dominance of electrostatic interactions and the occurrence of n→π* orbital delocalisation in C=O⋅⋅⋅C=O interactions. Abstract : Carbonyls reconciled : Electrostatics and orbital interactions have both been implicated in governing carbonyl interactions. A combined experimental and computational approach reconciles these conflicting explanations of the physiochemical origin of the interaction, demonstrating that orbital delocalisation augments electrostatic control, but for very close carbonyl contacts.